A review of antioxidant and anti-acetylcholinesterase activities of Centella asiatica (L.) Urb. for the treatment of Alzheimer’s disease - S., Abbas; M.S., Latif; N.S., Shafie; M.I., Ghazali; N.A.Z., Abidin; M.K., Mustafa; F., Kormin (2021)
Of many neurodegenerative diseases, Alzheimer’s disease (AD) is the most common cause of dementia globally, which is still incurable even after decades of extensive research to find a definite and permanent cure. Accumulation of free radicals and acetylcholine (ACh) deficiency in the brains of Alzheimer’s patients are considered as the factors leading to dementia and cognitive problems. This is by mechanisms involving disturbance in the balance between the amount of free radicals and the antioxidant defense system along with cholinergic deficit leading to impaired cholinergic neurotransmission. Currently available anti-AD drug therapy carries only the partial benefit of slowing down the progression of disease besides having various side effects and, hence, there is a developing interest to search for new drugs. Plants have always been of special interest in the field of new drug discovery research by virtue of their enormous biological diversity and tremendous potential of bioactive molecules. Many herbs are known to ameliorate the symptoms related to memory and cognitive disorders. Centella asiatica (L.) Urb. is one of the widely used plants claimed by the traditional system of medicine to have its positive effects on memory and brain functioning. The objective of this review is to present a comprehensive account on C. asiatica by summarizing the research until date related to its medicinal potential with a special focus on antioxidant and anti-acetylcholinesterase (anti- AChE) properties reflecting their potential therapeutic application for the treatment of AD.